Academic stress and emotional eating behaviour among IIUM students - Mohammad Radzi, Khairun Nisa’; Ibrahim, Muhamad Ariff; Saad, Nurulwahida; Mohd Nazori, Mohd Nazir; Shamsuddin, Aida Soraya (IIUM Press, 2022)
Introduction: Stress and pressure are inevitable events that occur in our life. Individuals at different stages of life perceived different types of stress, including adolescents. Academic stress has been identified as the main leading stress factor among teenagers. Therefore, to cater this stressful event, emotional eating behaviour is implemented as a response to the stimulation of the negative emotions perceived from this academic stress among students. Thus, this study is aimed to identify the prevalence of academic stress and its relationship with emotional eating behaviour among IIUM students. Method: A cross-sectional study was conducted, involving the collection of the 419 sample through simplerandom sampling among IIUM students from all campuses. A three-part self-administered questionnaire consisting of socio-demographic factor, Educational Stress Scale for Adolescent (ESSA) and Dutch Eating Behaviour Questionnaire (DEBQ) was used. Pearson correlationwas used to determine the relationship between the academic stress and emotional eating behaviour among the IIUM students. Result: The study showed that 39.6% of the students experienced low academic stress and 52.5% were on emotional eating status. Thisstudy also reported a significant relationship between academic stress and emotional eating behaviour (p < 0.001). Conclusion: Academic stress does affect the emotional eating behaviour of the IIUM students. Hence, the awareness on the healthy coping mechanism should be increased to ensure the positive impacts student’s life.